Effectiveness of the Numbered Heads Together Model in Enhancing Mathematics Learning Outcomes on Relations and Functions at the Junior High School Level - Desy Kristin Moonik; Vivian E. Regar; Murni Sulistyaningsih (Journal of Innovative and Creativity, 2025)
Goal. Improving the quality of mathematics learning outcomes remains a significant challenge in education, particularly for abstract topics such as relations and functions. This study aims to analyze the effectiveness of the Numbered Heads Together cooperative learning model in improving the mathematics learning outcomes of eighth-grade students at SMP PGRI Poopo.Materials and methods. This study employed a quantitative approach with a quasi-experimental One-Shot Case Study design involving 24 students. The treatment consisted of implementing the Numbered Heads Together learning model during the instructional process, after which students’ learning outcomes were measured through a posttest assessing their mastery of relations and functions concepts. Data were analyzed using descriptive statistics, the Liliefors normality test, and a one-sample t-test to determine whether the mean achievement exceeded the Minimum Mastery Criterion.Results. The analysis showed that the mean student learning outcome reached 83.83, with a minimum score of 70 and a maximum score of 95. The data distribution was confirmed to be normal. The calculated t-value of 6.65 significantly exceeded the critical t-value at the 0.05 significance level, indicating that students’ learning outcomes were above the Minimum Mastery Criterion. These findings demonstrate that the Numbered Heads Together model enhances student participation, conceptual understanding, and equitable engagement in learning activities.Conclusion. The implementation of the Numbered Heads Together model was proven effective in improving mathematics learning outcomes on relations and functions. This study strengthens empirical evidence on the benefits of cooperative learning in addressing abstract and deductive mathematical concepts and provides a basis for recommending the broader implementation of cooperative learning models to improve instructional quality at the secondary school level.